Sierra Leone : : Medical estimates - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Typescript and ms. correspondence and memoranda from Colonial Office and the administration in Sierra Leone, relating to expenditure on sanitation, health and medical services in the colony